Functional materials research II : selected, peer reviewed papers from the 2016 China Functional material Technology and Industry Forum, July, 25-28, 2016, Chongqing, China - Luo, Linqing; Huang, Guichun (Key engineering materials, 2017)
This book is the collection of results researches and engineering solutions in area of functional materials for various branches of modern manufacture which were represented on conference 2016 China Functional Material Technology and Industry Forum (CFMTIF 2016, July 25-28, 2016, Chongqing, China). Functional materials are generally characterized as those materials which possess the particular native properties and functions, including electrical, magnetic, optical, thermotic, acoustic, mechanic, chemical, biological functions. The development of functional materials is at the heart of technological needs and the forefront of materials research. Structural Materials, Alloys, Ceramics, Polymers and Composites, Semiconductors, Biomaterials, Materials for Energy Production and Energy Storage, Photocatalysis, Thin Films, Membranes, Coating Materials Materials Science.